DEMORALIZING OR EDUCATING? WAS THERE CHILDREN’S LITERATURE IN THE MIDDLE AGES? (ON THE BASIS OF “THE BOOK OF THE KNIGHT OF THE TOWER” BY GEOFFROI DE LA TOUR LANDRY) - Loba, Anna (Porównania, 2018)
“The Book of the Knight of the Tower” (1371–1372) is a pedagogical treatise compiled by a father concerned about the welfare and prospective good marriages of his daughters. It is difficult to match the educational and moral aims of the book to its content, which sometimes does not seem suitable for a child audience. However, the stories, which the narrator presents to young girls, invite us to reconsider whether “The Book” can be seen as an example of medieval literature for children.